Young Stellar Objects as possible counterparts of Fermi sources - Munar Adrover, Pere (2010)
Massive protostars have associated bipolar outflows which can produce strong shocks when in-teract with the surrounding medium. In these conditions particle acceleration up to relativistic velocities can occur leading to gamma-ray emission in subsequent interactions with ambient material, as some theoretical models predict. To identify young stellar objects (YSO) that may emit gamma rays we have crossed the Fermi First Year Catalog with some catalogs of known YSOs, and we have conducted Montecarlo simulations to find the probability of chance coinci-dence. We present a list of YSOs spatially coincident with Fermi sources and discuss which of these YSOs are better candidates than other sources in the field.